How Does Urbanization Affect Citizens’ Pro-Environment Behavior? A Hierarchical Analysis of the Chinese General Social Survey - Qing, Wen; Wang, Yibao; Zhang, Yanbo; Han, Jingwen; Li, Cuixi (Frontiers in Environmental Science, 2022)
Many studies have focused on the pressure of urbanization on resources and environment, but few have explored the positive effect of urbanization on reducing environmental pressure from the perspective of urbanization affecting pro-environment behavior (PEB). To systematically explore the impact of urbanization with different dimensions on PEB, this study constructs a hierarchical theoretical framework and carries out empirical test based on the data of Chinese General Social Survey (CGSS) and China Statistical Yearbook as well as a hierarchical linear model (HLM). The results reveal that the impacts of urbanization with different dimensions on PEB differ significantly. Economic urbanization can significant promote private PEB; social urbanization has a slightly positive impact on PEB; spatial urbanization has a notably negative impact on PEB and population urbanization has a slight impact on PEB. In addition, social and economic urbanizations positively moderate the relationship between social interaction and PEB. This means that urbanization not only directly affects PEB, but also moderates the relationship between individual characteristics and PEB. This new finding is of important theoretical significance for exploring the complex relationship between urbanization and PEB, and of certain practical reference value for the specific policy design to promote PEB.